Catalytic intense pulse light inactivation of Cronobacter sakazakii and other pathogens in non-fat dry milk and wheat flour. (1st December 2020) - Chen, Dongjie; Wiertzema, Justin R.; Peng, Peng; Cheng, Yanling; Wang, Yunpu; Liu, Juer; Ma, Yiwei; Mosher, Wes; Kang, Myungwoo; Min, Min; Chen, Paul; Baumler, David J.; et al.
Highlights: IPL intensity, pulsed duration, voltage affect the IPL disinfection capacity. This CIPL system causes higher disinfection on powdered foods compared with IPL alone. Significantly less changes were induced by IPL than UVC treatment on powdered foods. This pilot-scale CIPL system can fulfill the task of treating powder continuously. Abstract: The outbreaks of Cronobacter sakazakii, Salmonella spp, and Bacillus cereus in powdered foods have been increasing in worldwide. However, an effective method to pasteurize powdered foods before consumption remains lacking. A prototype Intense Pulsed Light (IPL) system was developed to disinfect powdered foods under different IPL and environmental conditions. Synergistic effect of IPL and TiO2 photocatalysis on microbial inactivation was studied. The results show that high energy intensity of each pulse, high peak intensity, and short pulsed duration contributed to a high microbe inactivation. With TiO2 photocatalysis, one additional log10 reduction was achieved, bringing the total log reduction to 4.71 ± 0.07 ( C. sakazakii ), 3.49 ± 0.01 ( E. faecium ), and 2.52 ± 0.10 ( B. cereus ) in non-fat dry milk, and 5.42 ± 0.10 ( C. sakazakii ), 4.95 ± 0.24 ( E. faecium ), 2.80 ± 0.23 ( B. cereus ) in wheat flour. IPL treatment combined with the TiO2 photocatalysis exhibits a strong potential to reduce the energy consumption in improving the safety of powdered foods.